Temporal resource partitioning of dung beetles (coleoptera: scarabaeidae: scarabaeinae) in the dung of two cow breeds in a tropical agroecosystem - Jomon, Mary; Rajagopal, Chitra; Anto, Anu; K. V., Vinod (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2021)
Dung beetles are important taxon as they decompose the excreta of higher animals, especially vertebrates. These coprophagous coleopterans are considered as biological indicators of healthy and clean ecosystems. Present study was aimed to describe the dung beetle diversity of an agroecosystem in Manjapra village, Ernakulam district of Kerala, South India, which is adjacent to forest areas. The study focused on the assessment of scarabs collected by using two different types of dung which is represented by Vechur (VC) and crossbred Jersey (CB) breeds. This was a preliminary study on dung beetle diversity in Vechur cow, a native breed of Kerala which could become extinct due to the increased preference for crossbred varieties. Identification and cataloguing of indigenous dung beetles associated with this native dung type is done for the first time. Since the dung beetle taxon is characterised by greater adaptability, possible strategies were studied with emphasis on its functional and temporal guild patterns. The sampling was carried out using bait-surface-grid pitfall traps with the dung types mentioned. The study recorded of 22 species of dung beetles belonging to six genera (Onthophagus, Copris, Oniticellus, Paracopris, Tibiodrepanus, Caccobius) under three tribes (Onthophagini, Coprini, Oniticellini). Temporal resource partition analysis recorded diurnal dung beetle preference towards crossbreed dung and nocturnal ones towards Vechur dung but with no significant difference (P>0.05). Functional guild composition of beetles showed the dominance of tunneller with Onthophagus favrei as the most dominant one. This study gives a glimpse on the checklist of dung beetles of the selected area and stresses the need to protect such agricultural patches in residential areas as potent microhabitats for scarabs and the whole insect community.